Cerium Titanate (Ce2Ti2O7): A Ferroelectric Ceramic with Perovskite‐Like Layered Structure (PLS). Issue 12 (2nd September 2015) - Gao, Zhipeng; Liu, Lixin; Han, Xu; Meng, Xiangfu; Cao, Linhong; Ma, Guohua; Liu, Yusheng; Yang, Jia; Xie, Qinghai; He, Hongliang
Abstract : A perovskite‐like layer‐structured compound, Ce2 Ti2 O7, was prepared in the argon atmosphere using solid reaction process. Single phase and dense Ce2 Ti2 O7 ceramic was fabricated by high‐pressure sintering at 4 GPa and 1100°C. This compound is unstable in oxygen/air when temperature is above 400°C, but it is stable under argon/vacuum. Differential scanning calorimetry result shown Ce2 Ti2 O7 has a phase transition at 1073°C, which might be the Curie point. The ferroelectricity of Ce2 Ti2 O7 was confirmed by the piezoelectric activity after poling ( d 33 = 0.4 ± 0.2 pC/N) for the first time.